Integration of Project Management with the Proposed Stage-Gate: The Tuning Project Case Report - Sabino, Michelle de Stefano (2011)
This paper aims to describe and to analyze the integration observed in the Sintonia project with respect to the comparison of project management processes to the model of the Stage-Gate ®. The literature addresses these issues conceptually, but lack an alignment between them that is evident in practice. As a method was used single case study. The report is as if the Sintonia project, developed by PRODESP - Data Processing Company of São Paulo. The results show the integration of project management processes with the Stage-Gate model developed during the project life cycle. The formalization of the project was defined in stages in which allowed the exploitation of economies of repetition and recombination to the development of new projects. This study contributes to the technical vision in dealing with the integration of project management processes. It was concluded that this system represents an attractive way, in terms of creating economic value and technological innovation for the organization.